Analysis Distance Learning System with Quantitative Descriptive Methods - Sukhbir Singh; Felix Widarko; Johan Libby; Kelvin; Mardi Turnip (Institute of Computer Science (IOCS), 2021)
The COVID-19 pandemic is currently very influential in all fields. One of them is in the field of education, where learning is usually carried out with a Face-to-Face Learning System must be changed to a Distance Learning System (DLS).To solve this problem, you can use various applications such as: Zoom, Google Classroom, Go To Meeting, Cisco Webex Meetings, Google Meet, and others. However, in the implementation of this activity there are still many problems.This study aims to analyze the Distance Learning System using quantitative descriptive methods. Based on the research results, it can be seen how effective the distance learning system that is being carried out now.